CT and MRI Imaging Features and Grades of Liver Iron Deposition - Huang Qianwen (ITM Web of Conferences, 2019)
CT and MRI imaging features and grades of liver iron deposition（LID）were discussed and evaluated in clinical application.The imaging and laboratory data of 20 patients with LID were analyzed retrospectively. CT value of liver were measured and MR signal intensity ratio of muscle/liver calculated.A new imaging grade of LID were made with CT and MR, and the grade correlation was analyzed between CT, MR and SF. All of 20 patients with LID, 19 cases were CT examination, their CT value ranging of liver were from 55HU to 116HU, of which more than 72HU were in 7 cases and 72HU or less in 12. 14 cases were MR examination with the low signal of liver, and the inverse phase signal of T1WI was higher than that of the positive phase. There were no significant difference among the grade of CT, T1WI, T2WI and SF (P>0.05), and there were the positive correlation of grade between CT, T1WI, T2WI and SF (rs=0.803,0.847,0.677 respectively), and of values between CT, T1WI SIR, T2WI SIR and SF(rs=0.454, 0.538, 0.811 respectively). CT can show the LID with high-density, but the mild LID can be with normal density, which is the false negative. MRI can show LID with low-signal, of which T2WI is the lower than T1WI, it is beneficial to diagnose the early LID. Grades of CT and MR have good consistent with that of SF, and can reflect the severity of LID, particularly that of MR-T1WI grading.